Relationships between Maladaptive Perfectionism towards Life Satisfaction among Undergraduate Students: Mediating Roles of Academic Engagement and Perceived Teacher Support - Thapatiwong, Archabaramee (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
The purposes of this study were 1) to examine the relationship between maladaptive perfectionism and life satisfaction among undergraduate students and 2) to analyze the mediating roles of academic engagement and perceived teacher support in the relationship between maladaptive perfectionism and life satisfaction among undergraduate students. Data was collected from 392 undergraduate students who enrolled in the 2024 academic year within Chiang Mai University obtained by multi-stage sampling. The research instruments consisted of the assessment forms of Life Satisfaction, Perfectionism, Academic Engagement, and Perceived Teacher Support, with reliability coefficients of .81, .89, .86, and .90 respectively. Statistical data was analyzed by descriptive statistics, correlation analysis and indirect effects in mediation analysis utilizing the SPSS Program with PROCESS Macro (Model 4) The results indicated a significant negative correlation between maladaptive perfectionism and life satisfaction (β = -.150, p < .001). A significant partial mediation was also found from academic engagement and perceived teacher support in the relationship between maladaptive perfectionism and life satisfaction (β = -.070, p < .001 and β = -.057, p < .001 respectively).